Monitoring Habitat Fragmentation and Biodiversity in Forest Ecosystems - Mazziotta, Adriano; Francini, Saverio; Parisi, Francesco (Springer, 2025)
The current biodiversity crisis is primarily caused by habitat loss and fragmentation, which are exacerbated by global population expansion and land use intensification. The techniques applied to evaluate the impact of habitat loss and fragmentation in forest ecosystems tend to measure changes in landscape patterns induced by forest degradation. Earth observation techniques and remotely sensed imagery are crucial tools for the large-scale monitoring of forest habitat loss and fragmentation along with related changes in forest biodiversity characteristics. Recently, the relevance of remote sensing for monitoring forest fragmentation has been further amplified by new satellite missions providing up-to-date and high-resolution open-access data available on cloud computing platforms. However, while satellite programmes like Landsat that employ remote sensing techniques are suitable for large-scale monitoring of forest species distribution, they cannot capture micro-spatial variations, since their sensors cannot disentangle forest heterogeneity. Finally, remotely sensed canopy-level information alone cannot fully explain biodiversity patterns. Integration of remote sensing and ground survey activities may help to overcome the limitations of these techniques, providing solutions for designing and optimizing monitoring strategies to tackle forest fragmentation and biodiversity loss in forest ecosystems.
Keywords: remote sensing; habitat; Google; land use; biodiversity